Venetoclax added to CLAG regimen might improve the outcome of patients with relapsed/refractory acute myeloid leukemia - Yu Zhang; Zhao Yin; Zurong Yao; Dan Xu; Xuejie Jiang; Xiaqi Nie; Dandan Chen; Hongsheng Zhou; Pengcheng Shi; Hui Liu; Qifa Liu; Guopan Yu (Therapeutic Advances in Hematology)
Background: We aim to analyze the efficacy and safety of Venetoclax (Ven) added to cladribine + cytarabine + granulocyte colony-stimulating factor (G-CSF) ± idarubicin or mitoxantrone (CLAG ± Ida/Mito) regimen as a salvage treatment of relapsed/refractory acute myeloid leukemia (RR-AML). Methods: A single-center, retrospective, cohort study was performed. Patients with RR-AML, being treated with CLAG ± Ida/Mito with versus without Ven, were retrospectively studied. The endpoints of this study were to evaluate the rate of composite complete remission (CRc), measurable residual disease (MRD), event-free survival (EFS), overall survival (OS), and relapse between CLAG and CLAG + Ven groups. Results: Sixty-nine patients were included, with a median age of 37 (range, 18–65) years. Thirty-one patients underwent one cycle of salvage treatment of CLAG ± Ida/Mito with Ven and 38 without. In the CLAG + Ven group, 24 (77.4%) patients acquired response, including 22 (71.0%) with composite complete remission (CRc) and 15 (48.4%) MRD-negative CRc, which was significantly higher than those (CRc 47.4%, p = 0.048; MRD-negative CRc 18.4%, p = 0.008) in the CLAG group. Subgroup analysis showed that patients without response after two courses of induction therapy, or patients with FLT3 mutations seemed to benefit more from CLAG ± Ida/Mito + Ven than CLAG ± Ida/Mito in acquiring CRc. With a median follow-up of 13 (95% CI 10.5–15.5) months, the CLAG + Ven group had a median OS of 22.9 (95% CI 19.6–26.2) months and EFS of 15.7 (95% CI 11.1–20.2) months. In contrast, the CLAG group had a median OS of 18.6 (95% CI 14.7–22.6) months and EFS of 10.7 (95% CI 6.6–14.8) months. Although not statistically significant, patients in the CLAG + Ven group showed a potential survival advantage compared to the CLAG group. AEs including all grade and grade 3/4 occurred at similar frequencies in the two groups. Conclusions: Ven added to CLAG ± Ida/Mito might improve the outcome of the patients with RR-AML, with well toleration, and a randomized controlled trial is needed to explored.